A preparation method of weather-resistant polyurethane resin and its application in powder coating
By modifying titanium dioxide nanoparticles and oxidizing chitosan oxidation treatment, combined with the application of composite nanomaterials, the problem of poor performance of traditional polyurethane coatings under ultraviolet light is solved, and the weather resistance and coating effect of polyurethane resin are significantly improved. .
Patent Information
- Application Number
- CN202410719492.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-05
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-06-05
AI Technical Summary
Traditional polyurethane coatings are prone to yellowing and powdering problems under ultraviolet exposure, resulting in insufficient weather resistance, especially in harsh environments, and poor service life and performance.
The surface of titanium dioxide nanoparticles was modified by in-situ hydrolysis condensation using tetraethyl silicate, and the ultraviolet absorber of methoxycinnamate was encapsulated in titanium dioxide porous by photopolymerization and emulsion polymerization. In the microspheres, oxidized chitosan and Schiff base modified chitosan are combined to form composite nanomaterials to improve the weather resistance of polyurethane resin.
It significantly improves the UV resistance, anti-aging and thermal stability of polyurethane resin, avoids environmental pollution of traditional solvent-based coatings, and provides a more uniform and efficient coating effect.
Smart Images

Figure BDA0004876626000000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane resins, in particular to a preparation method of a weather-resistant polyurethane resin and application of the same in powder coatings. Background Art
[0002] With the development of industry, the demand for coatings in protecting and decorating the surface of materials is growing. Especially in outdoor applications, coatings need to have excellent weather resistance to resist erosion by environmental factors such as sunlight, rain, and temperature changes. Polyurethane resin has become one of the key materials for high-performance coatings due to its excellent mechanical properties, chemical tolerance and flexible synthesis process. However, traditional polyurethane coatings still have room for improvement in weather resistance, especially long-term exposure to ultraviolet rays, which can easily cause yellowing and powdering.
[0003] To this end, researchers are committed to developing a new type of weather-resistant polyurethane resin to improve its service life and performance in harsh environments. This resin can significantly improve the UV resistance and anti-aging ability of the coating by improving the molecular structure and introducing monomers with excellent weather resistance. Using it as a basis in the field of powder coatings can not only avoid the environmental pollution problems of traditional solvent-based coatings, but also provide a more uniform and efficient coating effect.
[0004] Therefore, it is of great significance to invent a method for preparing a weather-resistant polyurethane resin and its application in powder coatings. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a weather-resistant polyurethane resin and application thereof in powder coatings, so as to solve the problems raised in the above-mentioned background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A method for preparing a weather-resistant polyurethane resin comprises the following steps:
[0008] S1: Heat 2% v / v glacial acetic acid solution to 60-65°C, add chitosan, stir for 1-1.5h, and cool to room temperature; add sodium periodate, and react at room temperature for 2-2.5h in the dark; add anhydrous ethanol to terminate the reaction, dialyze to obtain a chitosan intermediate; add the chitosan intermediate to glacial acetic acid, stir evenly, and soak at room temperature for 2-2.5h; add an oxidant, seal, and oxidize at room temperature; add anhydrous ethanol to terminate the reaction, filter, wash, and dry to obtain oxidized chitosan;
[0009] S2: adding oxidized chitosan and 5-chlorosalicylaldehyde to dimethyl sulfoxide, adding molecular sieves, heating to 55-60°C for reaction for 12-14 hours, adding the reaction product to acetone for precipitation, washing, and freeze-drying to obtain Schiff base modified chitosan;
[0010] S3: adding the titanium dioxide encapsulated porous microspheres to a 2% v / v acetic acid solution, stirring evenly, adding the solution to a 2% v / v acetic acid solution of oxidized chitosan, stirring for 1-2 hours, filtering, washing, and vacuum drying to obtain a composite nanomaterial;
[0011] S4: Add isophorone diisocyanate and polytetramethylene glycol to dimethyl sulfoxide, stir evenly, add stannous octoate catalyst, heat to 80-85°C and react for 30-45 minutes; add 1,4-butanediol and dimethyl sulfoxide solution of borate chain extender, keep warm and react for 1.5-2 hours; add trimethylolpropane and dimethyl sulfoxide solution of hindered phenol chain extender, keep warm and react for 1.5-2 hours; add Schiff base modified chitosan and dimethyl sulfoxide solution of composite nanomaterials, keep warm and react for 1.5-2 hours, vacuum desolventize to obtain weather-resistant polyurethane resin.
[0012] Furthermore, the method for preparing the titanium dioxide encapsulated porous microspheres comprises the following steps:
[0013] Step (1): ultrasonically dispersing titanium dioxide nanoparticles in an ethanol solution, heating to 80-85° C., and adjusting the pH of the system to 9-9.5 to obtain a suspension; uniformly adding an ethanol solution of tetraethyl silicate and an ammonia ethanol deionized water solution to the suspension, and after the addition is complete, heat-retaining the suspension for 3-3.5 hours, centrifuging, washing, drying, grinding and sieving to obtain silicon dioxide-coated titanium dioxide nanoparticles;
[0014] Step (2): ultrasonically dispersing the silica-coated titanium dioxide nanoparticles in an ethanol solution, heating to 80-85° C., adding γ-methacryloxypropyltrimethoxysilane, keeping warm and stirring for 24 hours, centrifuging, washing, drying, grinding and sieving to obtain silane coupling agent modified titanium dioxide nanoparticles;
[0015] Step (3): add trimethylolpropane triacrylate, aliphatic polyurethane hexaacrylate, photoinitiator, isooctyl p-methoxycinnamate, and silane coupling agent-modified titanium dioxide nanoparticles into dichloromethane, disperse by ultrasonication, transfer the reaction system into a 2% v / v polyvinyl alcohol solution, emulsify for 10-15 minutes, heat to 30-40° C. and stir for 5-5.5 hours, UV-curing for 10-15 minutes, filter, wash, and dry to obtain titanium dioxide encapsulated porous microspheres.
[0016] Furthermore, in the silica-coated titanium dioxide nanoparticles, the mass ratio of titanium dioxide nanoparticles: tetraethyl silicate: ammonia water is (5-8): (0.39-0.62): (0.9-1.44); the time for uniform addition is 6-8 hours; in the silane coupling agent modified titanium dioxide nanoparticles, the mass ratio of silica-coated titanium dioxide nanoparticles: γ-methacryloxypropyltrimethoxysilane is 1: (0.5-2); in the titanium dioxide encapsulated porous microspheres, the mass ratio of trimethylolpropane triacrylate: aliphatic polyurethane hexaacrylate: isooctyl p-methoxycinnamate: silane coupling agent modified titanium dioxide nanoparticles is (0.25-0.5): (0.03-0.05): (0.4-0.6): (0.15-0.25).
[0017] Furthermore, the preparation method of the hindered phenol chain extender comprises the following steps:
[0018] 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and trimethylolpropane are added to dichloromethane, stirred evenly, dicyclohexyl diimide and 4-dimethylaminopyridine are added, reacted at room temperature for 12-14 hours, filtered, washed, rotary evaporated, and vacuum dried to obtain a hindered phenol chain extender;
[0019] Furthermore, the molar ratio of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid:trimethylolpropane:dicyclohexyldiimide:4-dimethylaminopyridine is 1:1:1:1.
[0020] Furthermore, the preparation method of the borate chain extender comprises the following steps:
[0021] Add tetrahydroxymethylbenzeneboric acid and diethanolamine to N,N-dimethylformamide, heat to 40-45°C for reaction for 1-1.5h, wash, and recrystallize to obtain a chain extender intermediate; add the chain extender intermediate and isophorone diisocyanate to N,N-dimethylformamide, heat to 60-65°C for reaction for 2-2.5h under a nitrogen atmosphere, wash, and recrystallize to obtain a borate chain extender;
[0022] Furthermore, in the chain extender intermediate, the molar ratio of tetrahydroxymethylbenzeneboric acid:diethanolamine is 1:1; in the borate chain extender, the molar ratio of the chain extender intermediate:isophorone diisocyanate is 2:1.
[0023] Furthermore, in the chitosan intermediate, the mass ratio of chitosan to periodic acid is 4:(0.8-1); in the oxidized chitosan, the oxidation reaction time at room temperature is 3-4h.
[0024] Furthermore, in the Schiff base modified chitosan, the mass ratio of oxidized chitosan to 5-chlorosalicylaldehyde is (3.6-4.2):(1.8-2).
[0025] Furthermore, in the composite nanomaterial, the mass ratio of titanium dioxide encapsulated porous microspheres to oxidized chitosan is 1:(6-8).
[0026] Furthermore, in the weather-resistant polyurethane resin, the proportions of each component, by mass, are 30-35 parts of isophorone diisocyanate, 55-60 parts of polytetramethylene glycol, 0.3-0.4 parts of stannous octoate catalyst, 1-2 parts of 1,4-butanediol, 3-4 parts of borate chain extender, 1-2 parts of trimethylolpropane, 3-4 parts of hindered phenol chain extender, 2-3 parts of Schiff base modified chitosan, and 2-3 parts of composite nanomaterials.
[0027] Furthermore, in step S1, the oxidant is a mixed solution of nitric acid, phosphoric acid, and sodium nitrite in a mass ratio of 3.02:1.89:0.21;
[0028] Furthermore, the application of the weather-resistant polyurethane resin in powder coatings includes the following components: weather-resistant polyurethane resin, curing agent, leveling agent, brightener, and curing accelerator.
[0029] Furthermore, the curing agent is triglycidyl isocyanurate; the leveling agent is GLP588 universal leveling agent; the brightener is SC701, and the curing accelerator is triphenylethyl phosphonium bromide.
[0030] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0031] The present invention uses tetraethyl silicate to perform silicon dioxide coating modification on the surface of titanium dioxide nanoparticles through in-situ hydrolysis and condensation. The purpose is that the titanium dioxide nanoparticles after silicon dioxide coating modification can reduce the photocatalytic activity without sacrificing the ultraviolet shielding ability, thereby improving the weather resistance of polyurethane. In order to further improve the weather resistance of polyurethane and improve the dispersion performance of fillers in the matrix, the present invention uses the combined action of photopolymerization and emulsion polymerization to encapsulate the isooctyl p-methoxycinnamate ultraviolet absorber in titanium dioxide porous microspheres, and uses the advantages of porous microspheres to further improve the weather resistance of polyurethane through the "inside-outside" joint action.
[0032] The present invention performs oxidation treatment on chitosan so that its molecular structure contains a large number of carbonyl groups, and the II-II of the carbonyl groups *The invention uses oxidized chitosan as the basis, selects 5-chlorosalicylaldehyde to modify it, and prepares Schiff base modified chitosan; utilizes the n-Π generated by the C=N imine bond in the structure to generate a polyurethane matrix. * Electronic transition and π-π reaction of phenol in salicylaldehyde * Electron transition makes Schiff base modified chitosan have UV resistance; composite nanomaterials and Schiff base modified chitosan jointly extend the chain to further improve the weather resistance of polyurethane.
[0033] In order to further improve the weather resistance, it is not only necessary to improve the anti-ultraviolet performance, but also to improve the anti-oxidation performance and thermal stability. The present invention uses diethanolamine and tetrahydroxymethylbenzene boric acid to prepare a borate compound, which is then reacted with isophorone diisocyanate to successfully prepare a borate compound terminated with hydroxyl groups at both ends; it is introduced into the polyurethane prepolymer as a chain extender to improve the water resistance and thermal stability of the polyurethane; the present invention uses a carboxylic acid with a hindered phenol structure to react with trihydroxymethylpropane through an esterification reaction to prepare a diol with a hindered phenol structure, which is introduced into the polyurethane prepolymer as a chain extender to achieve the effect of improving the anti-oxidation and anti-aging of the polyurethane material. The purpose of improving the weather resistance of the polyurethane is achieved by utilizing the combined effect of the chain extenders. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] In the following examples, the titanium dioxide nanoparticles have a particle size of 300 nm and are purchased from Changzhou Quantong Chemical Co., Ltd.; the chitosan has a molecular weight of 70w and a deacetylation degree of ≥95%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; the polytetrahydrofuran has a molecular weight of 2000 and is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; the molecular sieve is type 4A, sodium type A, ≥φ0.5-1mm, Sinopharm Chemical Reagent Co., Ltd.; and the remaining raw materials are commercially available.
[0036] The method for preparing titanium dioxide nanoparticles modified by a silane coupling agent comprises the following steps:
[0037] Step (1): ultrasonically dispersing 5 g of titanium dioxide nanoparticles in an ethanol solution, heating to 80° C., adjusting the pH of the system to 9 to obtain a suspension; uniformly adding 50 mL of an ethanol solution containing 0.39 g of tetraethyl silicate and 50 mL of a deionized water solution containing 0.9 g of ammonia water and 1.1 g of ethanol to the suspension for 6 hours. After the addition is complete, the mixture is kept warm for 3 hours, centrifuged, washed, dried, ground and sieved to obtain silicon dioxide-coated titanium dioxide nanoparticles;
[0038] Step (2): ultrasonically dispersing 1 g of silica-coated titanium dioxide nanoparticles in an ethanol solution, heating to 80° C., adding 1 g of γ-methacryloxypropyltrimethoxysilane, keeping warm and stirring for 24 h, centrifuging, washing, drying, grinding and sieving to obtain silane coupling agent-modified titanium dioxide nanoparticles;
[0039] The preparation method of the hindered phenol chain extender comprises the following steps:
[0040] 1 mol of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and 1 mol of trimethylolpropane were added to dichloromethane, stirred evenly, 1 mol of dicyclohexyldiimide and 1 mol of 4-dimethylaminopyridine were added, reacted at room temperature for 12 hours, filtered, washed, rotary evaporated, and vacuum dried to obtain a hindered phenol chain extender;
[0041] The preparation method of the borate chain extender comprises the following steps:
[0042] 1 mol of tetrahydroxymethylbenzeneboric acid and 1 mol of diethanolamine were added to N,N-dimethylformamide, heated to 4045°C for reaction for 1 hour, washed, and recrystallized to obtain a chain extender intermediate; 2 mol of the chain extender intermediate and 1 mol of isophorone diisocyanate were added to N,N-dimethylformamide, heated to 60°C for reaction for 2 hours under a nitrogen atmosphere, washed, and recrystallized to obtain a borate chain extender;
[0043] Embodiment 1: A method for preparing a weather-resistant polyurethane resin: S1: Heat a 2% v / v glacial acetic acid solution to 60°C, add 4g of chitosan, stir for 1h, and cool to room temperature; add 0.8g of sodium periodate, and react at room temperature for 2h in the dark; add anhydrous ethanol to terminate the reaction, dialyze to obtain a chitosan intermediate; add 4g of the chitosan intermediate to glacial acetic acid, stir evenly, and soak at room temperature for 2h; add 15g of an oxidant, seal, and oxidize at room temperature for 3h; add anhydrous ethanol to terminate the reaction, filter, wash, and dry to obtain oxidized chitosan;
[0044] S2: 3.6 g of oxidized chitosan and 1.8 g of 5-chlorosalicylaldehyde were added to dimethyl sulfoxide, 4 g of molecular sieves were added, and the mixture was heated to 55°C for 12 h. The reaction product was added to acetone for precipitation, washed, and freeze-dried to obtain Schiff base modified chitosan;
[0045] S3: Add 1 g of titanium dioxide encapsulated porous microspheres to a 2% v / v acetic acid solution, stir evenly, add the solution to a 2% v / v acetic acid solution containing 6 g of oxidized chitosan, stir to react for 1 h, filter, wash, and vacuum dry to obtain a composite nanomaterial;
[0046] S4: 0.5 g trimethylolpropane triacrylate, 0.05 g aliphatic polyurethane hexaacrylate, 0.06 g photoinitiator 784, 0.4 g isooctyl p-methoxycinnamate, and 0.15 g silane coupling agent-modified titanium dioxide nanoparticles were added to dichloromethane, and ultrasonically dispersed. The reaction system was transferred to a 2% v / v polyvinyl alcohol solution, emulsified for 10 min, heated to 30° C. and stirred for 5 h, UV-cured for 10 min, filtered, washed, and dried to obtain titanium dioxide encapsulated porous microspheres;
[0047] S5: Add 30g of isophorone diisocyanate and 55g of polytetrahydrofuran diol to dimethyl sulfoxide, stir evenly, add 0.3g of stannous octoate catalyst, heat to 80°C and react for 30min; add a dimethyl sulfoxide solution containing 2g of 1,4-butanediol and 3g of borate chain extender, and keep warm for reaction for 1.5h; add a dimethyl sulfoxide solution containing 2g of trimethylolpropane and 3g of hindered phenol chain extender, and keep warm for reaction for 1.5h; add a dimethyl sulfoxide solution containing 2g of Schiff base modified chitosan and 2g of composite nanomaterials, keep warm for reaction for 1.5h, and vacuum desolventize to obtain a weather-resistant polyurethane resin.
[0048] Example 2: A method for preparing a weather-resistant polyurethane resin: S1: Heat a 2% v / v glacial acetic acid solution to 60°C, add 4g of chitosan, stir for 1h, and cool to room temperature; add 0.8g of sodium periodate, and react at room temperature for 2h in the dark; add anhydrous ethanol to terminate the reaction, dialyze to obtain a chitosan intermediate; add 4g of the chitosan intermediate to glacial acetic acid, stir evenly, and soak at room temperature for 2h; add 15g of an oxidant, seal, and oxidize at room temperature for 3h; add anhydrous ethanol to terminate the reaction, filter, wash, and dry to obtain oxidized chitosan;
[0049] S2: 3.6 g of oxidized chitosan and 2 g of 5-chlorosalicylaldehyde were added to dimethyl sulfoxide, 4 g of molecular sieves were added, and the mixture was heated to 55°C for 12 h. The reaction product was added to acetone for precipitation, washed, and freeze-dried to obtain Schiff base modified chitosan;
[0050] S3: adding 1 g of titanium dioxide encapsulated porous microspheres to a 2% v / v acetic acid solution, stirring evenly, adding the solution to a 2% v / v acetic acid solution containing 8 g of oxidized chitosan, stirring for 1 h, filtering, washing, and vacuum drying to obtain a composite nanomaterial;
[0051] S4: 0.5 g trimethylolpropane triacrylate, 0.05 g aliphatic polyurethane hexaacrylate, 0.06 g photoinitiator 784, 0.4 g isooctyl p-methoxycinnamate, and 0.15 g silane coupling agent-modified titanium dioxide nanoparticles were added to dichloromethane, and ultrasonically dispersed. The reaction system was transferred to a 2% v / v polyvinyl alcohol solution, emulsified for 10 min, heated to 30° C. and stirred for 5 h, UV-cured for 10 min, filtered, washed, and dried to obtain titanium dioxide encapsulated porous microspheres;
[0052] S5: Add 30g of isophorone diisocyanate and 55g of polytetrahydrofuran diol to dimethyl sulfoxide, stir evenly, add 0.3g of stannous octoate catalyst, heat to 80°C and react for 30min; add a dimethyl sulfoxide solution containing 2g of 1,4-butanediol and 3g of borate chain extender, and keep warm for reaction for 1.5h; add a dimethyl sulfoxide solution containing 2g of trimethylolpropane and 3g of hindered phenol chain extender, and keep warm for reaction for 1.5h; add a dimethyl sulfoxide solution containing 2g of Schiff base modified chitosan and 2g of composite nanomaterials, keep warm for reaction for 1.5h, and vacuum desolventize to obtain a weather-resistant polyurethane resin.
[0053] Example 3: A method for preparing a weather-resistant polyurethane resin: S1: Heat a 2% v / v glacial acetic acid solution to 60°C, add 4g of chitosan, stir for 1h, and cool to room temperature; add 0.8g of sodium periodate, and react at room temperature for 2h in the dark; add anhydrous ethanol to terminate the reaction, dialyze to obtain a chitosan intermediate; add 4g of the chitosan intermediate to glacial acetic acid, stir evenly, and soak at room temperature for 2h; add 15g of an oxidant, seal, and oxidize at room temperature for 3h; add anhydrous ethanol to terminate the reaction, filter, wash, and dry to obtain oxidized chitosan;
[0054] S2: 3.6 g of oxidized chitosan and 2 g of 5-chlorosalicylaldehyde were added to dimethyl sulfoxide, 4 g of molecular sieves were added, and the mixture was heated to 55°C for 12 h. The reaction product was added to acetone for precipitation, washed, and freeze-dried to obtain Schiff base modified chitosan;
[0055] S3: adding 1 g of titanium dioxide encapsulated porous microspheres to a 2% v / v acetic acid solution, stirring evenly, adding the solution to a 2% v / v acetic acid solution containing 8 g of oxidized chitosan, stirring for 1 h, filtering, washing, and vacuum drying to obtain a composite nanomaterial;
[0056] S4: 0.25 g trimethylolpropane triacrylate, 0.03 g aliphatic polyurethane hexaacrylate, 0.06 g photoinitiator 784, 0.6 g isooctyl p-methoxycinnamate, and 0.25 g silane coupling agent-modified titanium dioxide nanoparticles are added to dichloromethane, and ultrasonically dispersed. The reaction system is transferred to a 2% v / v polyvinyl alcohol solution, emulsified for 10 min, heated to 30° C. and stirred for 5 h, UV-cured for 10 min, filtered, washed, and dried to obtain titanium dioxide encapsulated porous microspheres;
[0057] S5: Add 30g of isophorone diisocyanate and 55g of polytetrahydrofuran diol to dimethyl sulfoxide, stir evenly, add 0.3g of stannous octoate catalyst, heat to 80°C and react for 30min; add a dimethyl sulfoxide solution containing 2g of 1,4-butanediol and 3g of borate chain extender, and keep warm for reaction for 1.5h; add a dimethyl sulfoxide solution containing 2g of trimethylolpropane and 3g of hindered phenol chain extender, and keep warm for reaction for 1.5h; add a dimethyl sulfoxide solution containing 2g of Schiff base modified chitosan and 2g of composite nanomaterials, keep warm for reaction for 1.5h, and vacuum desolventize to obtain a weather-resistant polyurethane resin.
[0058] Example 4: A method for preparing a weather-resistant polyurethane resin: S1: Heat a 2% v / v glacial acetic acid solution to 60°C, add 4g of chitosan, stir for 1h, and cool to room temperature; add 0.8g of sodium periodate, and react at room temperature for 2h in the dark; add anhydrous ethanol to terminate the reaction, dialyze to obtain a chitosan intermediate; add 4g of the chitosan intermediate to glacial acetic acid, stir evenly, and soak at room temperature for 2h; add 15g of an oxidant, seal, and oxidize at room temperature for 3h; add anhydrous ethanol to terminate the reaction, filter, wash, and dry to obtain oxidized chitosan;
[0059] S2: 3.6 g of oxidized chitosan and 2 g of 5-chlorosalicylaldehyde were added to dimethyl sulfoxide, 4 g of molecular sieves were added, and the mixture was heated to 55°C for 12 h. The reaction product was added to acetone for precipitation, washed, and freeze-dried to obtain Schiff base modified chitosan;
[0060] S3: adding 1 g of titanium dioxide encapsulated porous microspheres to a 2% v / v acetic acid solution, stirring evenly, adding the solution to a 2% v / v acetic acid solution containing 8 g of oxidized chitosan, stirring for 1 h, filtering, washing, and vacuum drying to obtain a composite nanomaterial;
[0061] S4: 0.25 g trimethylolpropane triacrylate, 0.03 g aliphatic polyurethane hexaacrylate, 0.06 g photoinitiator 784, 0.6 g isooctyl p-methoxycinnamate, and 0.25 g silane coupling agent-modified titanium dioxide nanoparticles are added to dichloromethane, and ultrasonically dispersed. The reaction system is transferred to a 2% v / v polyvinyl alcohol solution, emulsified for 10 min, heated to 30° C. and stirred for 5 h, UV-cured for 10 min, filtered, washed, and dried to obtain titanium dioxide encapsulated porous microspheres;
[0062] S5: Add 30g of isophorone diisocyanate and 55g of polytetrahydrofuran diol to dimethyl sulfoxide, stir evenly, add 0.3g of stannous octoate catalyst, heat to 80°C and react for 30min; add a dimethyl sulfoxide solution containing 1g of 1,4-butanediol and 4g of borate chain extender, and keep warm for reaction for 1.5h; add a dimethyl sulfoxide solution containing 1g of trimethylolpropane and 4g of hindered phenol chain extender, and keep warm for reaction for 1.5h; add a dimethyl sulfoxide solution containing 3g of Schiff base modified chitosan and 3g of composite nanomaterials, keep warm for reaction for 1.5h, and vacuum desolventize to obtain a weather-resistant polyurethane resin.
[0063] Comparative Example 1: A method for preparing a weather-resistant polyurethane resin: S1: Heat a 2% v / v glacial acetic acid solution to 60°C, add 4g of chitosan, stir for 1h, and cool to room temperature; add 0.8g of sodium periodate, and react at room temperature for 2h in the dark; add anhydrous ethanol to terminate the reaction, dialyze to obtain a chitosan intermediate; add 4g of the chitosan intermediate to glacial acetic acid, stir evenly, and soak at room temperature for 2h; add 15g of an oxidant, seal, and oxidize at room temperature for 8h; add anhydrous ethanol to terminate the reaction, filter, wash, and dry to obtain oxidized chitosan;
[0064] The remaining steps are the same as those in Example 1.
[0065] Comparative Example 2: A method for preparing a weather-resistant polyurethane resin: S5: Add 30g of isophorone diisocyanate and 55g of polytetramethylene glycol to dimethyl sulfoxide, stir evenly, add 0.3g of stannous octoate catalyst, heat to 80°C and react for 30min; add a dimethyl sulfoxide solution containing 1g of trimethylolpropane and 4g of hindered phenol chain extender, and keep the temperature for reaction for 1.5h; add a dimethyl sulfoxide solution containing 3g of Schiff base modified chitosan and 3g of composite nanomaterials, keep the temperature for reaction for 1.5h, and vacuum desolventize to obtain a weather-resistant polyurethane resin;
[0066] The remaining steps are the same as those in Example 1.
[0067] Comparative Example 3: A method for preparing a weather-resistant polyurethane resin: S5: Add 30g of isophorone diisocyanate and 55g of polytetrahydrofuran diol to dimethyl sulfoxide, stir evenly, add 0.3g of stannous octoate catalyst, heat to 80°C for reaction for 30min; add a dimethyl sulfoxide solution containing 1g of 1,4-butanediol and 4g of a borate chain extender, and keep the temperature for reaction for 1.5h; add a dimethyl sulfoxide solution containing 3g of Schiff base-modified chitosan and 3g of a composite nanomaterial, keep the temperature for reaction for 1.5h, and vacuum desolventize to obtain a weather-resistant polyurethane resin;
[0068] The remaining steps are the same as those in Example 1.
[0069] Comparative Example 4: A method for preparing a weather-resistant polyurethane resin: S5: Add 30g of isophorone diisocyanate and 55g of polytetramethylene glycol to dimethyl sulfoxide, stir evenly, add 0.3g of stannous octoate catalyst, heat to 80°C and react for 30min; add a dimethyl sulfoxide solution containing 1g of 1,4-butanediol and 4g of a borate chain extender, and keep the temperature for reaction for 1.5h; add a dimethyl sulfoxide solution containing 1g of trimethylolpropane and 4g of a hindered phenol chain extender, keep the temperature for reaction for 1.5h, and vacuum desolventize to obtain a weather-resistant polyurethane resin;
[0070] The remaining steps are the same as those in Example 1.
[0071] Experiment: Powder coating was prepared according to the following components: 60g weather-resistant polyurethane resin, 14g triglycidyl isocyanurate curing agent, 1.5g leveling agent GLP588, 10.6g brightener SC70, 0.3g curing accelerator triphenylethyl phosphonium bromide; the powder coating was sprayed on the surface of the steel plate, heated to 200℃ for cross-linking and curing, and the coating thickness was 50μm;
[0072] Weather resistance test: Tested according to GB / T 1865-2009;
[0073] Impact resistance test: tested according to T / GDTL 004-2018;
[0074] Moisture and heat resistance test: Tested according to GB / T 1740
[0075] Table 1 Weathering polyurethane performance test data
[0076]
[0077] Conclusion: In Comparative Example 1, the oxidation reaction time is too long, resulting in an increase in by-products and a decrease in yield at the same mass. In the subsequent reaction process, there is a lack of sufficient reactants, resulting in reduced performance.
[0078] Comparative Example 2 lacks a borate chain extender; Comparative Example 3 lacks a hindered phenol chain extender; Comparative Example 4 lacks Schiff base-modified chitosan and composite nanomaterials, resulting in reduced mechanical properties and weather resistance.
[0079] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a weather-resistant polyurethane resin, characterized in that: The following steps are involved: S1: Heat 2% v / v glacial acetic acid solution to 60-65°C, add chitosan, stir for 1-1.5h, and cool to room temperature; add sodium periodate, and react at room temperature for 2-2.5h in the dark; add anhydrous ethanol to terminate the reaction, dialyze to obtain a chitosan intermediate; add the chitosan intermediate to glacial acetic acid, stir evenly, and soak at room temperature for 2-2.5h; add an oxidant, seal, and oxidize at room temperature; add anhydrous ethanol to terminate the reaction, filter, wash, and dry to obtain oxidized chitosan; S2: adding oxidized chitosan and 5-chlorosalicylaldehyde to dimethyl sulfoxide, adding molecular sieves, heating to 55-60°C for reaction for 12-14 hours, adding the reaction product to acetone for precipitation, washing, and freeze-drying to obtain Schiff base modified chitosan; S3: adding the titanium dioxide encapsulated porous microspheres to a 2% v / v acetic acid solution, stirring evenly, adding the solution to a 2% v / v acetic acid solution of oxidized chitosan, stirring for 1-2 hours, filtering, washing, and vacuum drying to obtain a composite nanomaterial; S4: adding isophorone diisocyanate and polytetramethylene glycol to dimethyl sulfoxide, stirring evenly, adding stannous octoate catalyst, heating to 80-85°C for reaction for 30-45 minutes; adding 1,4-butanediol and dimethyl sulfoxide solution of borate chain extender, keeping warm for reaction for 1.5-2 hours; adding trimethylolpropane and dimethyl sulfoxide solution of hindered phenol chain extender, keeping warm for reaction for 1.5-2 hours; adding Schiff base modified chitosan and dimethyl sulfoxide solution of composite nanomaterials, keeping warm for reaction for 1.5-2 hours, vacuum desolventizing, and obtaining weather-resistant polyurethane resin; In the oxidized chitosan, the oxidation reaction time at room temperature is 3-4h; The method for preparing titanium dioxide encapsulated porous microspheres comprises the following steps: Step (1): ultrasonically dispersing titanium dioxide nanoparticles in an ethanol solution, heating to 80-85° C., and adjusting the pH of the system to 9-9.5 to obtain a suspension; uniformly adding an ethanol solution of tetraethyl silicate, ammonia water, and an ethanol deionized water solution to the suspension, and after the addition is complete, heat-retaining the suspension for 3-3.5 hours, centrifuging, washing, drying, grinding, and sieving to obtain silicon dioxide-coated titanium dioxide nanoparticles; Step (2): ultrasonically dispersing the silica-coated titanium dioxide nanoparticles in an ethanol solution, heating to 80-85° C., adding γ-methacryloxypropyltrimethoxysilane, keeping warm and stirring for 24 hours, centrifuging, washing, drying, grinding and sieving to obtain silane coupling agent modified titanium dioxide nanoparticles; Step (3): adding trimethylolpropane triacrylate, aliphatic polyurethane hexaacrylate, photoinitiator, isooctyl p-methoxycinnamate, and titanium dioxide nanoparticles modified by a silane coupling agent to dichloromethane, and ultrasonically dispersing the mixture. Transferring the reaction system to a 2% v / v polyvinyl alcohol solution, emulsifying for 10-15 minutes, heating to 30-40° C. and stirring for 5-5.5 hours, UV curing for 10-15 minutes, filtering, washing, and drying to obtain titanium dioxide encapsulated porous microspheres; The preparation method of the hindered phenol chain extender comprises the following steps: 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid and trimethylolpropane are added to dichloromethane, stirred evenly, dicyclohexyl diimide and 4-dimethylaminopyridine are added, reacted at room temperature for 12-14 hours, filtered, washed, rotary evaporated, and vacuum dried to obtain a hindered phenol chain extender; The preparation method of the borate chain extender comprises the following steps: Tetrahydroxymethylbenzeneboric acid and diethanolamine are added to N,N-dimethylformamide, heated to 40-45°C for reaction for 1-1.5h, washed, and recrystallized to obtain a chain extender intermediate; the chain extender intermediate and isophorone diisocyanate are added to N,N-dimethylformamide, heated to 60-65°C for reaction for 2-2.5h under a nitrogen atmosphere, washed, and recrystallized to obtain a borate chain extender.
2. The method for preparing a weather-resistant polyurethane resin according to claim 1, characterized in that: In the silica-coated titanium dioxide nanoparticles, the mass ratio of titanium dioxide nanoparticles: tetraethyl silicate: ammonia water is (5-8):(0.39-0.62):(0.9-1.44); the time for uniform addition is 6-8h; in the silane coupling agent modified titanium dioxide nanoparticles, the mass ratio of silica-coated titanium dioxide nanoparticles:γ-methacryloxypropyltrimethoxysilane is 1:(0.5-2); in the titanium dioxide encapsulated porous microspheres, the mass ratio of trimethylolpropane triacrylate: aliphatic polyurethane hexaacrylate: isooctyl p-methoxycinnamate: silane coupling agent modified titanium dioxide nanoparticles is (0.25-0.5):(0.03-0.05):(0.4-0.6):(0.15-0.25).
3. The method for preparing a weather-resistant polyurethane resin according to claim 1, characterized in that: In the preparation process of the hindered phenol chain extender, the molar ratio of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid: trimethylolpropane: dicyclohexyl diimide: 4-dimethylaminopyridine is 1:1:1:
1.
4. The method for preparing a weather-resistant polyurethane resin according to claim 1, characterized in that: In the preparation process of the borate chain extender, in the chain extender intermediate, the molar ratio of tetrahydroxymethylbenzeneboric acid:diethanolamine is 1:1; in the borate chain extender, the molar ratio of the chain extender intermediate:isophorone diisocyanate is 2:
1.
5. The method for preparing a weather-resistant polyurethane resin according to claim 1, characterized in that: During the preparation of the chitosan intermediate, the mass ratio of chitosan to sodium periodate is 4:(0.8-1).
6. The method for preparing a weather-resistant polyurethane resin according to claim 1, characterized in that: In the preparation process of the Schiff base modified chitosan, the mass ratio of oxidized chitosan to 5-chlorosalicylaldehyde is (3.6-4.2):(1.8-2).
7. The method for preparing a weather-resistant polyurethane resin according to claim 1, characterized in that: During the preparation of the composite nanomaterial, the mass ratio of titanium dioxide encapsulated porous microspheres to oxidized chitosan is 1:(6-8).
8. The method for preparing a weather-resistant polyurethane resin according to claim 1, characterized in that: In the weather-resistant polyurethane resin, the proportions of various components, by mass, are 30-35 parts of isophorone diisocyanate, 55-60 parts of polytetramethylene glycol, 0.3-0.4 parts of stannous octoate catalyst, 1-2 parts of 1,4-butanediol, 3-4 parts of borate chain extender, 1-2 parts of trimethylolpropane, 3-4 parts of hindered phenol chain extender, 2-3 parts of Schiff base modified chitosan, and 2-3 parts of composite nanomaterials.
9. Weather-resistant polyurethane prepared according to the method for preparing a weather-resistant polyurethane resin according to any one of claims 1 to 8.
10. Use of the weather-resistant polyurethane resin according to claim 9 in powder coatings.
